Difference between revisions of "Math 22 Product Rule and Quotient Rule"

From Math Wiki
Jump to navigation Jump to search
Line 38: Line 38:
 
   denominator.
 
   denominator.
 
   <math>\frac{d}{dx}[\frac{f(x)}{g(x)}]=\frac{f'(x)g(x)-f(x)g'(x)}{[g(x)]^2}</math>
 
   <math>\frac{d}{dx}[\frac{f(x)}{g(x)}]=\frac{f'(x)g(x)-f(x)g'(x)}{[g(x)]^2}</math>
 +
 +
 +
'''Example''': Find derivative of
 +
 +
'''1)''' <math>f(x)=\frac{x}{x-5}</math>
 +
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Solution: &nbsp;
 +
|-
 +
|<math style="vertical-align: -5px">f'(x)=\frac{\frac{d}{dx}[x](x-5)-(x)\frac{d}{dx}[(x-5)]}{(x-5)^2}</math>
 +
|-
 +
|<math>=\frac{(1)(x-5)-x(1)}{(x-5)^2}=\frac{-5}{(x-5)^2}</math>
 +
|}
 +
 +
'''2)''' <math>f(x)=\frac{x^2}{x+3}</math>
 +
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Solution: &nbsp;
 +
|-
 +
|<math style="vertical-align: -5px">f'(x)=\frac{\frac{d}{dx}[x^2](x+3)-(x^2)\frac{d}{dx}[(x+3)]}{(x+3)^2}</math>
 +
|-
 +
|<math>=\frac{(2x)(x+3)-(x^2)(1)}{(x+3)^2}=\frac{2x^2+6x-x^2}{(x+3)^2}=\frac{x^2+6x}{(x+3)^2}</math>
 +
|}
 +
 +
'''3)''' <math>f(x)=(e^2+x^2)(4x+5)</math>
 +
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Solution: &nbsp;
 +
|-
 +
|<math style="vertical-align: -5px">f'(x)=\frac{d}{dx}[(e^2+x^2)](4x+5)+(e^2+x^2)\frac{d}{dx}[(4x+5)]</math>
 +
|-
 +
|<math>=(2x)(4x+5)+(e^2+x^2)(4)=8x^2+10x+4e^2+8x^2=-16x^2+10x+4e^2</math>
 +
|}
 +
 +
 +
 
[[Math_22| '''Return to Topics Page''']]
 
[[Math_22| '''Return to Topics Page''']]
  
 
'''This page were made by [[Contributors|Tri Phan]]'''
 
'''This page were made by [[Contributors|Tri Phan]]'''

Revision as of 08:34, 22 July 2020

The Product Rule

 The derivative of the product of two differentiable functions is equal to the first function times 
 the derivative of the second plus the second function times the derivative of the first.
 

Example: Find derivative of

1)

Solution:  

2)

Solution:  

3)

Solution:  

The Quotient Rule

 The derivative of the quotient of two differentiable functions is equal to the denominator times the derivative of the numerator minus the numerator times the derivative of the denominator, all divided by the square of the 
 denominator.
 


Example: Find derivative of

1)

Solution:  

2)

Solution:  

3)

Solution:  


Return to Topics Page

This page were made by Tri Phan